Comparison of Pre-Operative Intravenous Versus Oral Glucose Administration on Recovery Outcome in Post-Anesthesia Care Unit in Colorectal Surgery Patients - Sharif, Muhammad Huzaifa; Mateen, Osama; Haider, Syed Zeeshan; Khan, Taimur Azam; Tariq, Safwan Ahmed; Awan , Abrar Ahmed (Pakistan Armed Forces Medical Journal, 2025)
Objective: To explore the recovery outcome after pre-operative administration of glucose (Carbohydrate/Dextrose) in the oral versus intravenous form in patients undergoing elective colorectal surgery in the post-anesthesia care unit.Study Design: Quasi-experimental study.     Place and Duration of Study: Department of Anesthesiology, Combined Military Hospital Rawalpindi, Pakistan from Aug 2022-Jan 2023.Methodology: A Quasi-experimental study was conducted in which 160 patients were divided into two groups of 80 patients each. After the fasting duration of 8 hours, Group-O received 1 g/kg of Dextrose dissolved in 100 ml of normal saline administered orally 2 hours prior to surgery whereas Group-I received 1g/kg of Dextrose dissolved in 100 ml of Normal Saline administered intravenously 2 hours prior to surgery. Variables measured were post-operative pain on Visual Analog Scale (VAS), incidence of nausea, vomiting, thirst, hunger, fatigue, and anxiety.Results: Stay in recovery did not significantly change between both groups with 5.29±0.25 hours in the Intravenous group versus 5.28±0.27 hours in the Oral group (p 0.60). However, post-operative pain scales were significantly different with 3.28±0.57 versus 4.13±0.41 between both groups (p